Use of Noninvasive Ventilation with Volume-Assured Pressure Support in Neuralgic Amyotrophy with Bilateral Diaphragmatic Paralysis - Diaz-Abad, Montserrat (Open Respir Med J, 2019)
Neuralgic Amyotrophy (NA) is a rare, acute onset inflammatory brachial plexopathy that frequently presents with acute pain followed by shoulder girdle muscle weakness. Phrenic nerve involvement affecting the diaphragms occurs in 7-10% of cases. We present the case of a 52-year-old man with neuralgic amyotrophy with phrenic nerve involvement and bilateral diaphragmatic paralysis with marked respiratory symptoms and sleep hypoventilation, who was treated with non-invasive ventilation with volume assured pressure support mode. By 21 months post disease onset, the patient had experienced marked improvement in orthopnea, sleep quality and functional status. This is the first reported case of the use of this mode of noninvasive ventilation in neuralgic amyotrophy.